THE EFFECT OF ENTREPRENEURIAL ORIENTATION AND INNOVATION CAPABILITY TOWARDS FIRM PERFORMANCE IN SMALL AND MEDIUM ENTERPRISES (Case Study: Grilled Restaurants in Manado) - Mohammad, Inayah Nadzillah; Massie, James D.D; Tumewu, Ferdinand J. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Entrepreneurial orientation and innovation capability plays an important role in improving business performance and becomes an acceptable meaning to explain the firm performance. Most of the SMEs in Manado, they have a strong entrepreneurial orientation in their business. This research aims to identify the influence of entrepreneurial orientation and innovation capability towards firm performance. This research aims to focus on SMEs of grilled restaurant in Manado. This research using quantitative method. The examined population in this research are the owners of SMEs in Manado. The result of this research which is from questionnaire with 50 respondent shows that entrepreneurial orientation and innovation capability has a positive and significantly influence the firm performance simultaneously and partially. Researcher recommend For the owners to improve the performance of SMEs things that need to be considered and improved are the need for achievement, internal locus of control, self-reliance, and extroversion. Furthermore, Innovation is one of the important things towards firm performance, which is also has a positive impact on the process of innovation and performance. So that owners need to invest more in innovative capabilities and support efforts to introduce new types of innovation.Â Keyword : entrepreneurial orientation, innovation, and firm performance